1996
DOI: 10.1007/bf00016876
|View full text |Cite
|
Sign up to set email alerts
|

The impact of food quantity on UV-B tolerance and recovery from UV-B damage in Daphnia pulex

Abstract: UVB (290 nm) tolerance of Daphnia pulex, conditioned to four different food levels (Chlorophyta), was tested under standardized conditions with an artificial radiation source . Parameters measured were survival, percentage of egg bearing Daphnia and the number of juveniles produced after irradiation . LTV-B tolerance of Daphnia pulex was found to be significantly improved with increasing food concentrations at all three parameters . The impact of the four different food concentrations on the photoreactivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 10 publications
(9 reference statements)
1
19
0
Order By: Relevance
“…Considering these arguments, we suggest that UVR avoidance by vertical displacement may be more efficiently achieved in deep, stratified lakes than in shallow, continuously mixed ones. Of course, such a conclusion remains to be tested, and we acknowledge the fact that other factors, such as a better nutritional status, may contribute to UVR tolerance (Zellmer 1996).…”
Section: Physiological and Behavioral Responses To Par And Uvr-mentioning
confidence: 97%
“…Considering these arguments, we suggest that UVR avoidance by vertical displacement may be more efficiently achieved in deep, stratified lakes than in shallow, continuously mixed ones. Of course, such a conclusion remains to be tested, and we acknowledge the fact that other factors, such as a better nutritional status, may contribute to UVR tolerance (Zellmer 1996).…”
Section: Physiological and Behavioral Responses To Par And Uvr-mentioning
confidence: 97%
“…Therefore, herbivore consumers living in transparent lakes would be constrained by poor stoichiometric food quality and would also be exposed to a potentially hazardous UVR regime. Early studies on Daphnia pulex have suggested that better nutritional status may contribute to a greater UVR tolerance (Zellmer 1996). Andean lakes are characterized by the high transparency and high UVR penetration (Morris et al 1995).…”
mentioning
confidence: 99%
“…Our estimate of the relative lethal dose for D. magna was higher than that of Hurtubise et al (1998). This variation could be due to our different experimental set up or differences in food quality, which are known to influence UVB tolerance of cladocerans (Zellmer 1996). Also respiration rates (Fischer et al 2006) and temperature (Moresino, and Helbling 2010) can affect the lethal UVB dose.…”
Section: Discussionmentioning
confidence: 99%